The Impact of Ramadan Fasting on the Cardiovascular System with Particular Emphasis on Myocardial Infarction Risk - Olczyk, Liwia; Więcko, Laura; Trela, Katarzyna; Tuteja, Aleksander; Burzykowska, klaudia; Geborys, Kamila; Krupa, Konrad; Mohaissen, Rema; Tyla, Mikołaj; Stabrawa, Patryk (Quality in Sport, 2026)
Introduction Cardiovascular diseases (CVD) are the leading cause of death worldwide, with prevalence rising in aging populations. Ramadan fasting, practiced by over a billion Muslims annually, may influence cardiovascular health through changes in metabolism and lifestyle. Aim of the Study This study aims to assess the effects of Ramadan fasting on the cardiovascular system, with emphasis on the risk of myocardial infarction. Materials and Methods This is a narrative literature review of current studies examining the impact of Ramadan fasting on cardiovascular parameters such as glucose metabolism, lipid profile, blood pressure, and incidence of cardiovascular events. Results Most studies suggest that Ramadan fasting leads to favorable changes: improved lipid profile, lower blood pressure, and reduced inflammation. Fasting appears safe for individuals with stable cardiovascular disease under medical supervision. However, a slight increase in myocardial infarction cases has been noted after Ramadan in some subgroups, especially older adults and those with comorbidities like diabetes or hypertension. Conclusion Ramadan fasting may benefit cardiovascular health, but safety depends on individual risk factors. It should be avoided by patients with unstable heart conditions. Personalized assessment and increased awareness are key to safe fasting practices.